Record makers and breakers : voices of the independent rock 'n' roll pioneers - Broven, John (Music in American life., 2009)
This volume is a history of the independent rock 'n' roll record industry from its raw regional beginnings in the 1940s with R & B and hillbilly music through its peak in the 1950s and decline in the 1960s. John Broven combines narrative history with extensive oral history material from numerous recording pioneers including Joe Bihari of Modern Records; Marshall Chess of Chess Records; Jerry Wexler, Ahmet Ertegun, and Miriam Bienstock of Atlantic Records; Sam Phillips of Sun Records; Art Rupe of Specialty Records; and many more. --From publisher's description.